Late Pleistocene submarine mass movements: occurrence and causes - Owen, M; Day, S; Maslin, M (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
An extensive study of Late Pleistocene continental slope submarine mass movements was undertaken. Twenty-six well-dated mass movements occurred during the last 45 ka BP in the North Atlantic sector. A latitudinal trend is observed: between 45 and 12 ka BP most events occur in the mid- to low-latitudes, post- 12 ka BP high-latitude occurring events dominate. A cluster of events is associated with the Last Glacial sea level lowstand and Termination 1B. Further events are associated with Termination 1A and the Holocene. Prior to 23 ka BP no clear relationship with the ice core atmospheric methane record is observed, in contrast during and following the deglaciation there is a possible relationship with atmospheric methane. High-latitude mass movements are primarily controlled by cyrospheric-induced variations in sedimentation and local sea level. In high latitudes, the glaciation subdues mass movement activity through reduced seisimicity, sediment supply and ocean temperatures. Deglaciation increases the sediment supply, seisimicity and ocean temperatures, thus increasing the likelihood of continental slope failures. For example the Storegga event coincides with high isostatic uplift and postglacial seisimicity, while the Andoya and Tr ae nadjupet events occur before and after the peak rates respectively. In contrast low latitudes experience greater risk of slope failures during glacial periods from falling sea levels, although during the deglacial and interglacial period there is a potential for failure from changes in deposition centres and rates, as well as warming ocean temperatures potentially leading to dissociation of gas hydrates. The ongoing rapid deglaciation of coastal Greenland and Antarctica and consequent rapid input of sediment, isostatic uplift, crustal stress release and warming bottom water temperature at the shelf break will increase the risk of continental slope failure in these regions. (c) 2007 Elsevier Ltd. All rights reserved.